2003
DOI: 10.1289/ehp.5928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the isoflavones genistein and equol on the gonadal development of Japanese medaka Oryzias latipes.

Abstract: The estrogenic isoflavone compound genistein recently has been found in the effluents of sewage treatment plants and pulp mills, and the related compound equol has been detected in the runoff from agricultural fields treated with hog manure. Waterborne exposures of Japanese medaka (Oryzias latipes) to equol from soon after hatch to approximately 100 days posthatch induced gonadal intersex (i.e., testis-ova) in males at incidences of 10 and 87% in equol treatments of 0.4 and 0.8 µg/L, respectively. Exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 63 publications
6
75
1
Order By: Relevance
“…Concentration of all quantified phytoestrogens were lower than hazardous levels described in the in vivo experiments of Kiparissis et al (2003). In this study, only concentrations of GEN above 1000 lg L -1 produced gonadal intersex in the Japanese medaka (Oryzias latipes).…”
Section: Ecotoxicological Revelancecontrasting
confidence: 50%
“…Concentration of all quantified phytoestrogens were lower than hazardous levels described in the in vivo experiments of Kiparissis et al (2003). In this study, only concentrations of GEN above 1000 lg L -1 produced gonadal intersex in the Japanese medaka (Oryzias latipes).…”
Section: Ecotoxicological Revelancecontrasting
confidence: 50%
“…, it is possible that estrogenic endocrine disruption may be induced locally by this phytoestrogen, as reported by others (Kiparissis et al 2003). Endocrine disruption can also be induced by the phytosterol SITO, which is structurally similar to cholesterol.…”
Section: Phytoestrogens and Sitosterolmentioning
confidence: 64%
“…For example, in female fathead minnows exposed to the aromatase inhibitor fadrozole for 21 d there was a significant reduction in histologically determined ovarian stage, and reduced vitellogenin uptake into developing oocytes (Ankley et al, 2002). Jensen et al (2004) reported increased numbers of early stage follicles and atretic follicles in female fathead minnows exposed to the anti-androgen flutamide for 21 d. Weisbrod et al (2007) reported increased numbers of previtellogenic oocytes and decreased proportions of early and late vitellogenic oocytes in female fathead minnows exposed to >1.2 mg benzophenone-2/L or to 50 ng 17␣-ethynylestradiol for 15 d. Similar types of effects have been observed in zebrafish and medaka (Kiparissis et al, 2003;van der Ven et al, 2003). Such shifts in the relative proportions of differently staged follicles may reflect effects of the chemicals on the fish reproductive axis, and at the same time obscure aspects of the transcript profile that could yield mechanistic insights.…”
Section: Introductionmentioning
confidence: 63%